Preparation method of elemental organic polymer type high-temperature-resistant retarder
By introducing inorganic elements phosphorus, silicon, and boron into the traditional organic polymer retarder, and using the adsorption properties of boric acid groups and phosphoric acid groups, the problem of easy degradation of traditional retarders at high temperatures is solved, and the high temperature stability and construction safety of cement slurry are achieved.
Patent Information
- Application Number
- CN202510093343.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-21
AI Technical Summary
Traditional organic polymer retarders are prone to degradation at high temperatures, resulting in the oil well cement slurry being centered and stepped, affecting the safety of cementing construction.
通过在传统有机聚合物类缓凝剂中引入无机元素磷(P)、硅(Si)、硼(B),形成更稳定的化学键,提高聚合物的热稳定性,并通过硼酸基、磷酸基的吸附性增强水泥浆的高温缓凝效果。
It significantly improves the high-temperature resistance of the retarder, avoids the phenomenon of centering and stepping of the cement slurry at high temperatures, and ensures the safe pumping and cementing quality of the cement slurry.
Smart Images

Figure CN119823320A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cementing materials, and specifically relates to a method for preparing a high-temperature resistant retarder for cementing, and in particular to a method for preparing an element organic polymer type high-temperature resistant retarder. Background Art
[0002] In recent years, with the exploration and development of deep and ultra-deep oil and gas resources, oil well cement retarders need to have excellent high temperature resistance and slow setting properties to ensure the safe pumping of cement slurry. However, traditional organic polymer retarders are prone to degradation at high temperatures, resulting in unstable cement slurry performance, core encapsulation and stepping, which seriously affects the construction safety of oil and gas well cementing.
[0003] At present, traditional organic polymer retarders are usually polymerized from 2-acrylamido-2-methylpropanesulfonic acid AMPS and acid monomers such as acrylic acid AA and itaconic acid IA. AMPS has been widely used in the preparation of retarders due to its excellent high temperature resistance, salt resistance, environmental friendliness, excellent retarding performance and low dosage sensitivity (Lu Ya, Li Ming, Guo Zihan, et al. Overview of the research status of polymer oil well cement retarders [J]. Plastic Industry, 2016, (2): 23-26, 33). However, this type of retarder is easily degraded under high temperature conditions, resulting in abnormal phenomena of core encapsulation and stepping in cement slurry (Li Ming, Zhang Junsong, Yu Yongjin, et al. A high temperature resistant broad-spectrum environmentally friendly retarder for cementing and its preparation method and application: 202411270237.1 [p]. 2014-10-18). However, inorganic retarders such as boric acid and its salts are extremely sensitive to the dosage, which is not conducive to the control of cement slurry thickening time (Yu Yang. Preparation and retarding mechanism of metal-chelate retarders for oil well cement [D]. Chengdu: Southwest Petroleum University. 2021).
[0004] The present invention introduces inorganic elements phosphorus (P), silicon (Si), and boron (B) into the traditional organic polymer retarder to form a more stable chemical bond and improve the thermal stability of the polymer. In addition, the boric acid group and the phosphoric acid group have a great influence on the Ca in the cement slurry. 2+ It has stronger adsorption capacity, which helps to enhance the high-temperature retarding effect of cement slurry, so that oil well cement can still maintain good working performance under high temperature conditions, effectively avoid the occurrence of core and stepping phenomena, and improve the construction quality and service life of oil and gas well cementing. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing an elemental organic polymer type high temperature resistant retarder. The method has reliable principle, simple operation, cheap and readily available raw materials, and a controllable preparation process. The prepared retarder has excellent stability in a high temperature environment of 120-205°C, and its temperature resistance is greatly improved compared with that of traditional pure carbon chain polymer retarders, thereby overcoming the defects and shortcomings of the prior art and having broad market application prospects.
[0006] Another object of the present invention is to provide the application of the elemental organic polymer type high temperature resistant retarder in cementing cement slurry. The retarder has good high temperature resistance and good compatibility, can effectively regulate the thickening time of cement slurry, ensure the safe pumping of cement slurry during cementing construction, and effectively improve the success rate of cementing.
[0007] In order to achieve the above technical objectives, the present invention adopts the following technical solutions.
[0008] First, vinyl silane is hydrolyzed to generate silanol, and a monomer containing a boric acid group or a phosphoric acid group in the side chain is obtained through a polycondensation reaction of Si-OH with OH in boric acid or phosphoric acid; then the carbon-carbon double bond in the obtained monomer is subjected to a polyaddition reaction with 2-acrylamide-2-methylpropanesulfonic acid (AMPS) to obtain a gel-like substance with a certain viscosity; finally, it is purified with anhydrous ethanol, repeatedly washed with deionized water, and then freeze-dried and ground into powder to obtain an elemental organic polymer type high temperature resistant retarder. By introducing inorganic elements Si, P, and B, the retarder has good high temperature resistance and good compatibility compared with traditional organic retarders. It can effectively regulate the thickening time of cement slurry at 120~205℃, ensure the safe pumping of cement slurry during cementing construction, and overcome the phenomenon of cement slurry core and stepping caused by the easy degradation of traditional retarders at high temperatures.
[0009] An elemental organic polymer type high temperature retardant, with vinyl silane, inorganic acid (boric acid or phosphoric acid), 2-acrylamido-2-methylpropanesulfonic acid (AMPS) as raw materials, using the redox initiation system H2O2 / V C , prepared and synthesized by free radical aqueous solution polymerization.
[0010] A method for preparing an elemental organic polymer type high temperature resistant retarder comprises the following steps in sequence: (1) Weigh a certain amount of vinyl silane, dissolve it in deionized water, add an organic acid to adjust the solution to a pH of 3 to 4, stir until the solution is clear, and obtain a vinyl silane hydrolyzate. Add an inhibitor solution dropwise thereto, wherein the amount of the inhibitor added is 1% of the mass of the vinyl silane; (2) Add a certain amount of inorganic acid solution into a three-necked flask equipped with a stirring device and a thermometer. The inorganic acid is boric acid or phosphoric acid. When the temperature reaches 45-55°C, add vinyl silane hydrolyzate and stir to react for 6-8 hours to obtain liquid A. (3) Add a certain amount of AMPS and deionized water to a three-necked flask equipped with a stirring device and a thermometer, start stirring, and after AMPS is fully dissolved, add H2O2 and stir for 15 minutes; (4) Weigh chain transfer agent, V C and deionized water to obtain liquid B, wherein the chain transfer agent, V C The amount of H2O2 added is 0.2%, 0.5% and 0.5% of the mass of AMPS respectively, and liquid A and liquid B are added dropwise to the solution of step (3) at a uniform speed; (5) After the addition is complete, add NaOH solution to adjust the pH value to within the range of 4 to 6, and react at 60 to 70 °C for 3 to 6 hours; (6) The solution obtained after the reaction in step (5) is extracted with anhydrous ethanol, the extract is repeatedly washed with deionized water, and then freeze-dried to obtain an elemental organic polymer type anti-high temperature retarder.
[0011] Furthermore, the vinyl silane is one or more of vinyl trimethoxy silane, vinyl triethoxy silane, vinyl tri(2-methoxyethoxy) silane, 7-octenyl trimethoxy silane, and styrene ethyl trimethoxy silane.
[0012] Furthermore, the organic acid is one or more of formic acid, acetic acid, citric acid and oxalic acid.
[0013] Furthermore, the polymerization inhibitor is hydroquinone, 2-tert-butyl-1,4-benzoquinone, 2,6-di-tert-butylphenol, 1,1-diphenyl-2-picrylhydrazyl or 1,4-benzoquinone.
[0014] Furthermore, the molar ratio of the vinyl silane, AMPS and inorganic acid is 3-6: 4-7: 2-5. By adjusting the ratio between the reaction monomers, a series of elemental organic polymer-type high temperature retarders can be synthesized.
[0015] Furthermore, the chain transfer agent is 3-mercaptopropionic acid, isopropanol, sodium formate, 2-methyl-2-[(dodecylthiocarbonyl)thio]propionic acid, dithiocarbamate or 2,6-di-tert-butyl-p-cresol.
[0016] Furthermore, the application of the elemental organic polymer type anti-high temperature retarder refers to using it as an admixture in cementing cement slurry, and the addition amount of the elemental organic polymer type anti-high temperature retarder is 0.3~5.0% of the total mass of oil well cement and admixtures.
[0017] The reaction process of the elemental organic polymer type high temperature resistant retarder is as follows (taking vinyl trimethoxysilane, boric acid and AMPS as an example):
[0018] The AMPS used in the present invention is a commonly used monomer for the synthesis of oilfield chemical admixtures, has excellent temperature resistance, salt resistance and hydrolysis stability, and has a certain slow setting property for oil well cement. The silane coupling agent has a special molecular structure, has both groups that can react with inorganic materials and groups that can combine with organic materials, and has a good application effect on organic polymer / inorganic functional hybrid materials. The present invention successfully introduces inorganic slow setting groups into organic AMPS polymers through the polycondensation reaction between the silane coupling agent and the inorganic acid. From the perspective of bond energy, the average bond energy of the Si-O bond is 530.9 kJ / mol, the average bond energy of the BO bond is 515 kJ / mol, the average bond energy of the PO bond is 410 kJ / mol, and the average bond energy of the CC bond is 332 kJ / mol, so the organic hybrid polymer retarder obtained by the present invention has better high temperature resistance than traditional carbon chain polymers.
[0019] Compared with the prior art, the present invention has the advantages of: (1) The present invention significantly improves the high temperature resistance of the retarder by introducing atoms such as Si, P, and B, and can stably work in a high temperature environment of 120-205°C, thereby improving the abnormal gelation phenomena such as cement slurry core encapsulation and step formation caused by the easy degradation of traditional organic polymer retarders; (2) The present invention can effectively improve the fluidity of cement slurry, avoid the low-temperature thickening of cement slurry caused by traditional organic polymer retarders, and ensure the safe pumping and cementing quality of cement slurry; (3) The phosphoric acid and boric acid groups introduced by the present invention have an effect on the Ca2+ content in cement slurry. 2+ The chelation and adsorption effects of the polymer enhance the retarding performance. Compared with the main adsorption group -COO - , phosphate and borate groups to Ca 2+ The chelating and adsorption effects are stronger, which can avoid the decarboxylation caused by the use of AMPS and acid monomers in traditional polymer retarders at high temperatures, and is conducive to improving the temperature resistance of traditional AMPS-based polymer retarders; (4) The present invention combines the excellent retarding effect of phosphoric acid and boric acid retarders, avoids the problem of their dosage sensitivity, has good compatibility with other admixtures, and can accurately control the thickening time of cement slurry. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is the thickening curve of the oil well cement slurry prepared by adding the high temperature resistant retarder of Example 1.
[0021] Figure 2 This is the thickening curve of the oil well cement slurry prepared by adding the high temperature resistant retarder of Example 2.
[0022] Figure 3 This is the thickening curve of the oil well cement slurry prepared by adding the high temperature resistant retarder of Example 3.
[0023] Figure 4 This is the thickening curve of the oil well cement slurry prepared by adding the high temperature resistant retarder of Example 4.
[0024] Figure 5 This is the thickening curve of the oil well cement slurry prepared by adding the high temperature resistant retarder of Comparative Example 1.
[0025] Figure 6 This is the thickening curve of the oil well cement slurry prepared by adding the high temperature resistant retarder of Comparative Example 2. DETAILED DESCRIPTION
[0026] The purpose, technical scheme and advantages of the present invention are further described below in conjunction with the accompanying drawings and examples. The raw materials used in the examples are all commercially available, but the embodiments of the present invention are not limited thereto. Example 1
[0027] (1) Weigh 22.24 g of vinyltrimethoxysilane and deionized water, add a certain amount of acetic acid to adjust the solution pH to 3.5, stir at 2000 r / min until the solution is clear to obtain a vinyltrimethoxysilane hydrolyzate, and then add 1% hydroquinone (based on the mass of vinyltrimethoxysilane); (2) Add 6.19 g of boric acid to a 500 mL three-necked flask equipped with a stirring device and a thermometer, heat to 70°C until completely dissolved, cool to 50°C, add the liquid obtained in step (1), and stir at 1200 r / min for 8 h to obtain liquid A; (3) Add 41.45 g of AMPS and deionized water to a 500 mL three-necked flask equipped with a stirring device and a thermometer. Start stirring. After AMPS is fully dissolved, add 0.5% H2O2 (based on the mass of AMPS) and stir for 15 min. (4) Weigh 3-mercaptopropionic acid, V C and deionized water to prepare liquid B (3-mercaptopropionic acid, V C The mass of the two solutions is 0.2% and 0.5% of the mass of AMPS respectively), and at the same time, liquid A and liquid B are added dropwise to the liquid in (3) at a uniform speed; (5) After the addition of liquid A and liquid B was completed, NaOH solution was added to adjust the pH value to 5, and the reaction was stirred at 65°C and 1200 r / min for 4 h; (6) The solution obtained after the reaction in step (5) is extracted with anhydrous ethanol, and the extract is repeatedly washed with deionized water until the filtrate is neutral, and then freeze-dried and the product is ground into powder to obtain an elemental organic polymer type anti-high temperature retarder. Example 2
[0028] (1) Weigh 19.03 g of vinyl triethoxysilane and deionized water, add a certain amount of formic acid to adjust the solution pH to 3.2, stir at 2000 r / min until the solution is clear to obtain a vinyl triethoxysilane hydrolyzate, and then add 1% 2-tert-butyl-1,4-benzoquinone (based on the mass of vinyl triethoxysilane); (2) Add 4.64 g of boric acid to a 500 mL three-necked flask equipped with a stirring device and a thermometer, heat to 70°C until completely dissolved, cool to 55°C, add the liquid obtained in step (1), and stir at 1200 r / min for 6 h to obtain liquid A; (3) Add 25.91 g of AMPS and deionized water to a 500 mL three-necked flask equipped with a stirring device and a thermometer. Start stirring. After AMPS is fully dissolved, add 0.5% H2O2 (based on the mass of AMPS) and stir for 15 min. (4) Weigh isopropanol, V C and deionized water to prepare liquid B (isopropanol, V C The mass of the two solutions is 0.2% and 0.5% of the mass of AMPS respectively), and at the same time, liquid A and liquid B are added dropwise to the liquid in (3) at a uniform speed; (5) After the addition of liquid A and liquid B was completed, NaOH solution was added to adjust the pH value to 4.5, and the mixture was stirred at 60°C and 1200 r / min for 6 h; (6) The solution obtained after the reaction in step (5) is extracted with anhydrous ethanol, and the extract is repeatedly washed with deionized water until the filtrate is neutral, and then freeze-dried and the product is ground into powder to obtain an elemental organic polymer type anti-high temperature retarder. Example 3
[0029] (1) Weigh 28.04 g of vinyl tris(2-methoxyethoxy)silane and deionized water, add a certain amount of oxalic acid to adjust the solution pH to 3.0, stir at 2000 r / min until the solution is clear to obtain a vinyl tris(2-methoxyethoxy)silane hydrolyzate, and then add 1% 2,6-di-tert-butylphenol (based on the mass of vinyl tris(2-methoxyethoxy)silane); (2) Add 7.84 g of phosphoric acid to a 500 mL three-necked flask equipped with a stirring device and a thermometer. When the temperature reaches 45°C, add the liquid obtained in step (1) and stir at 1200 r / min for 7 h to obtain liquid A. (3) Add 24.87 g of AMPS and deionized water to a 500 mL three-necked flask equipped with a stirring device and a thermometer. Start stirring. After AMPS is fully dissolved, add 0.5% H2O2 (based on the mass of AMPS) and stir for 15 min. (4) Weigh sodium formate, V C and deionized water to prepare liquid B (sodium formate, V C The mass of the two solutions is 0.2% and 0.5% of the mass of AMPS respectively), and at the same time, liquid A and liquid B are added dropwise to the liquid in (3) at a uniform speed; (5) After the addition of liquid A and liquid B was completed, NaOH solution was added to adjust the pH value to 5.5, and the mixture was stirred at 70°C and 1200 r / min for 3 h; (6) The solution obtained after the reaction in step (5) is extracted with anhydrous ethanol, and the extract is repeatedly washed with deionized water until the filtrate is neutral, and then freeze-dried and the product is ground into powder to obtain an elemental organic polymer type anti-high temperature retarder. Example 4
[0030] (1) Weigh 30.29 g of styrene ethyl trimethoxy silane and deionized water, add a certain amount of citric acid to adjust the solution pH to 4.0, stir at 2000 r / min until the solution is clear to obtain styrene ethyl trimethoxy silane hydrolyzate, and then add 1% 1,4-benzoquinone (based on the mass of styrene ethyl trimethoxy silane); (2) Add 7.84 g of phosphoric acid to a 500 mL three-necked flask equipped with a stirring device and a thermometer, add the liquid obtained in step (1) when the temperature reaches 50°C, and stir at 1200 r / min for 8 h to obtain liquid A; (3) Add 29.01 g of AMPS and deionized water to a 500 mL three-necked flask equipped with a stirring device and a thermometer. Start stirring. After AMPS is fully dissolved, add 0.5% H2O2 (based on the mass of AMPS) and stir for 15 min. (4) Weigh 2,6-di-tert-butyl-p-cresol, V C and deionized water to prepare liquid B (2,6-di-tert-butyl-p-cresol, V C The mass of the two solutions is 0.2% and 0.5% of the mass of AMPS respectively), and at the same time, liquid A and liquid B are added dropwise to the liquid in (3) at a uniform speed; (5) After the addition of liquid A and liquid B was completed, NaOH solution was added to adjust the pH value to 6.0, and the mixture was stirred at 65°C and 1200 r / min for 4 h; (6) The solution obtained after the reaction in step (5) is extracted with anhydrous ethanol, and the extract is repeatedly washed with deionized water until the filtrate is neutral, and then freeze-dried and the product is ground into powder to obtain an elemental organic polymer type anti-high temperature retarder.
[0031] 2. Performance test of an elemental organic polymer type high temperature retardant Preparation Comparative Example 1: (1) Using deionized water as solvent, according to the molar ratio of AMPS, IA (itaconic acid), AA (acrylic acid), and SSS (sodium styrene sulfonate) of 7:4:4:3, 36.27 g AMPS, 13.01 g IA, 7.21 g AA, and 15.46 g SSS were weighed and dissolved in deionized water, with a solute mass fraction of 30%. Stir for about 15 to 30 min to completely dissolve them; (2) Adjust the pH value to 6.0 with NaOH solution, transfer to a three-necked flask equipped with a mechanical stirrer, a thermometer, and a condenser, and heat to 60 °C; (3) Add 0.5% of the total mass of the monomer, potassium persulfate solution, into the flask at a rate of one drop every 3 to 4 seconds and react at a constant temperature for 6 hours to obtain a liquid retarder.
[0032] Preparation Comparative Example 2: (1) Using deionized water as solvent, weigh 41.45 g AMPS, 8.67 g IA, 7.21 g AA, and 20.62 g SSS respectively and dissolve them in deionized water according to the molar ratio of AMPS, IA, AA, and SSS of 6:2:3:3. The mass fraction of solute is 30%. Stir for about 15 to 30 min to make them completely dissolved. (2) Adjust the pH value to 4.0 with NaOH solution, transfer to a three-necked flask equipped with a mechanical stirrer, a thermometer, and a condenser, and heat to 65 °C; (3) Add 0.3% of the total mass of the monomer, potassium persulfate solution, into the flask at a rate of one drop every 3 to 4 seconds, and react at a constant temperature for 4 hours to obtain a liquid retarder.
[0033] The retarders of Examples 1 to 4 and Comparative Examples 1 to 2 were added to the oil well cement respectively, and the basic formula of the cement slurry was: Jiahua G-grade oil well cement + 30% quartz sand (200 mesh) + 5% microsilicon + 0.5% dispersant (USZ) + 2.5% fluid loss reducer (SD130) + 3.5% retarder + 2.0% suspension stabilizer (SD89) + water, wherein SD130 and SD89 were provided by Sichuan Chuanqing Downhole Technology Co., Ltd., and USZ was provided by Weihui Chemical Co., Ltd. The mass percentages of each component were calculated based on Jiahua G-grade oil well cement, and the water-cement ratio was 0.44. The thickening time, fluidity and other properties of the oil well cement slurry were measured, and the results are shown in Table 1. The thickening time test conditions were 205°C*130MPa*120min.
[0034]
[0035] It can be seen from Table 1 that the thickening time of the cement slurry in Examples 1 to 4 at 3.5% addition meets the thickening time requirement of cementing, and there is no core or bulging phenomenon; while the thickening time of Comparative Examples 1 and 2 is prolonged, and there are bulging and stepping phenomena.
[0036] Figures 1 to 4 They are respectively the thickening curves of cement slurries prepared by adding Examples 1 to 4, Figures 5 and 6 They are respectively the thickening curves of cement slurries prepared by adding comparative examples 1 and 2. As can be seen from the figure, the consistency curves of the cement slurries using embodiments 1 to 4 are basically stable, with only a small fluctuation within the normal range, no step phenomenon, and the initial consistency values are all below 30Bc, and have good right-angle thickening characteristics; while the consistency of the cement slurry using comparative example 1 drops significantly after 1.5 hours, and after entering the insulation stage, the temperature curve fluctuates continuously, i.e., the core phenomenon; the consistency of the cement slurry using comparative example 2 increases and decreases suddenly between 1 and 1.5 hours, i.e., the step phenomenon, which is not conducive to the development of cementing operations.
[0037] The element organic polymer type high temperature resistant retarder prepared in Example 1 was used to prepare oil well cement slurry, and the basic formula of cement slurry was: Jiahua G grade oil well cement + 30% quartz sand (200 mesh) + 5% microsilicon + 0.5% dispersant (USZ) + 2.5% fluid loss reducer (SD130) + 1.5% suspension stabilizer (SD89) + water, and the water-cement ratio was 0.44. By controlling the amount of retarder added, it was verified whether the cement slurry thickening time results at 120-205°C met the requirements, and the results are shown in Table 2.
[0038]
[0039] It can be clearly seen from the data in Table 2 that the elemental organic polymer type high temperature resistant retarder of Example 1 has a good linear relationship of dosage, which is convenient for construction personnel to accurately control the thickening performance of cement slurry according to actual needs. In the wide temperature range of 120~205℃, the retarder of the present invention can effectively delay the thickening time of cement slurry, thereby ensuring that the cement slurry has ideal pumpability during the entire cementing process. It is suitable for cementing operations in long sealing sections, deep wells, and ultra-deep wells.
[0040] The high temperature retarders of Examples 1 to 4 and the retarders prepared in Comparative Examples 1 to 2 were applied to oil well cement, and commercially available dispersants USZ, SXY-2, fluid loss reducers SD130, and G33S were compounded to test the fluidity and fluid loss reduction of cement slurry and evaluate its admixture compatibility. SXY-2 was provided by Chengdu Chuanfeng Chemical Engineering Co., Ltd., and G33S was provided by Weihui Chemical Co., Ltd. The basic formula of cement slurry is: Jiahua G-grade oil well cement + 30% quartz sand (200 mesh) + 5% microsilicon + 1.0% dispersant + 5.0% fluid loss reducer + 2.0% suspension stabilizer + water, with a water-cement ratio of 0.44.
[0041]
[0042] As can be seen from Table 3, the compatibility of the high temperature resistant retarders and the fluid loss reducers of Examples 1 to 4 is good, and the water loss of the oil well cement slurries prepared therefrom is below 50 mL, while the water loss of the oil well cement slurries prepared using the retarders of Comparative Examples 1 and 2 is above 50 mL, and the compatibility is not good.
[0043] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalents cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing an elemental organic polymer type high temperature resistant retarder, comprising the following steps in sequence: (1) dissolving vinyl silane in deionized water, adding an organic acid to adjust the solution to a pH of 3 to 4, stirring until the solution becomes clear to obtain a vinyl silane hydrolyzate, and dropping a polymerization inhibitor into the solution; (2) Add an inorganic acid solution, such as boric acid or phosphoric acid, to a three-necked flask equipped with a stirring device and a thermometer, and add vinyl silane hydrolyzate when the temperature reaches 45-55°C. Stir and react for 6-8 hours to obtain liquid A; (3) Add AMPS and deionized water to a three-necked flask equipped with a stirring device and a thermometer, start stirring, and after AMPS is fully dissolved, add H2O2 and stir for 15 minutes; (4) Weigh chain transfer agent, V C and deionized water to obtain solution B, and at the same time, dropwise add solution A and solution B to the solution in step (3) at a uniform speed; (5) After the addition is complete, add NaOH solution to adjust the pH value to within the range of 4 to 6, and react at 60 to 70 °C for 3 to 6 hours; (6) The solution obtained after the reaction in step (5) is extracted with anhydrous ethanol, the extract is washed with deionized water, and then freeze-dried to obtain an elemental organic polymer type anti-high temperature retarder.
2. The method for preparing an elemental organic polymer type high temperature resistant retarder according to claim 1, characterized in that: The vinyl silane is one or more of vinyl trimethoxy silane, vinyl triethoxy silane, vinyl tri(2-methoxyethoxy) silane, 7-octenyl trimethoxy silane, and styrene ethyl trimethoxy silane.
3. The method for preparing an elemental organic polymer type high temperature resistant retarder according to claim 1, characterized in that: The organic acid is one or more of formic acid, acetic acid, citric acid and oxalic acid.
4. The method for preparing an elemental organic polymer type high temperature resistant retarder according to claim 1, characterized in that: The polymerization inhibitor is hydroquinone, 2-tert-butyl-1,4-benzoquinone, 2,6-di-tert-butylphenol, 1,1-diphenyl-2-picrylhydrazyl or 1,4-benzoquinone.
5. The method for preparing an element organic polymer type high temperature resistant retarder as claimed in claim 4, characterized in that: The amount of the polymerization inhibitor added is 1% of the mass of the vinyl silane.
6. The method for preparing an elemental organic polymer type high temperature resistant retarder according to claim 1, characterized in that: The molar ratio of the vinyl silane, AMPS and inorganic acid is 3-6:4-7:2-5.
7. The method for preparing an elemental organic polymer type high temperature resistant retarder according to claim 1, characterized in that: The chain transfer agent is 3-mercaptopropionic acid, isopropanol, sodium formate, 2-methyl-2-[(dodecylthiocarbonyl)thio]propionic acid, dithiocarbamate or 2,6-di-tert-butyl-p-cresol.
8. The method for preparing an elemental organic polymer type high temperature resistant retarder according to claim 1, characterized in that: The chain transfer agent, V C The added amounts of H2O2 are 0.2%, 0.5% and 0.5% of the mass of AMPS respectively.
9. The elemental organic polymer type anti-high temperature retarder prepared by the method according to claim 1, 2, 3, 4, 5, 6, 7 or 8 is used as an admixture in cementing cement slurry, and the addition amount of the elemental organic polymer type anti-high temperature retarder is 0.3-5.0% of the total mass of oil well cement and admixtures.
Citation Information
Patent Citations
Vinyl acetate-ethylene copolymer emulsion and method for producing same
CN107864655A
Inorganic-organic polymer oil well cement retarding agent, and preparation method and application thereof
CN109503781A
Silane-polymer-containing oil well cement dispersant and preparation method and application thereof
CN111978001A
Dispersing agent for oil well cement and application thereof
CN114075314A
Retarder as well as preparation method and application thereof
CN116410421A